就寝中覚醒の確率過程モデリング - 脳波による視床-皮質間結合強度の解析結果から - 岸, 哲史; 中村, 亨; 山口, 郁博; 東郷, 史治; 山本, 義春 (Transactions of Japanese Society for Medical and Biological Engineering, 2016)
Waking during nocturnal sleep (WS) is gaining attention in the health science field. Although some findings, (e.g., the power-law distribution of the wake duration time) have been reported, the mechanism of it is still unclear. In this talk, we light on this issue. In a previous study, we showed that corticothalamic feedback loop strength (c2), estimated by an EEG analysis method, clearly tracks the wake-to-sleep transition just before nocturnal sleep. This time, we applied this method to nocturnal sleep. The c2-distribution (n = 52) during nocturnal sleep exhibited clear bimodal, which can be well approximated by superposition of two Gaussian distributions corresponding to sleep (Non-REM 1-4 and REM) and wake states, respectively. This observation suggests that the dynamical change of c2 obeys the Ornstein-Uhlenbeck process in each state. Based on these findings, we show an attempt for stochastic process modeling of WS.